Perbandingan Implementasi Kebijakan Gubernur Sulawesi Barat dalam Meningkatkan Pembangunan Jalan Poros Salutambung-Aralle - Gaus, Muhammad; Tamma, Sukri; Yunus, Ariana (LP2M IAIN Palopo, 2022)
Policy implementation is the most crucial stage of the policy process because, at this stage, benefits will be obtained from previously defined concepts. Regarding the policy for the construction of the Salutambung-Aralle axis, the steps taken were to compare the implementation of the policies of the Governor of West Sulawesi in each period so that the efforts and obstacles of each Governor were found in that period. The research method used is a qualitative approach with a descriptive analysis type. The study results show that during the reign of Anwar Adnan Saleh, efforts to increase the construction of the road got an excellent basis after changing its status from a district road to a provincial strategic highway. Meanwhile, during the administration of the Governor of ABM, policy planning was quite good. Still, it did not have a strong commitment at the implementation stage, as evidenced by various obstacles, including passing incompetent contractors and a lack of communication involving the community.